Under the Gaze of Ra: Surveillance and Subjection in Sonallah Ibrahim’s The Committee and Basma Abdel Aziz’s The Queue - Abdelmotagally, Noha; Abdelsalam, Samar; Abdelrahman, Fadwa (Surveillance & Society, 2026)
This paper examines how surveillance socially controls individuals and designates them as subjects in Sonallah Ibrahim’s The Committee (2001) and Basma Abdel Aziz’s The Queue (2016b), employing surveillance studies and Louis Althusser’s (1971) theory of state apparatuses—focusing equally on both repressive state apparatuses (RSAs) and ideological state apparatuses (ISAs)—and concept of interpellation as its theoretical framework. In The Committee, interpellation is enforced through the state apparatuses; characters internalize their being under the constant gaze of the State and develop a kind of self-discipline that ensures their automatic conformity to the dominant ideology. Similarly, The Queue portrays the effects of social control and surveillance on individuals. The queue becomes a symbol of the complete subjection of the people to the almost incomprehensible dictates of the authoritarian regime. By analyzing the dynamics of power and the interplay of surveillance and/by the state apparatuses in these two novels, this paper demonstrates how surveillance operates as a powerful mechanism of social control, shaping individual consciousness and behavior in profound ways. It highlights the enduring relevance of surveillance studies in understanding the complex relationship between the power of the gaze and individual subjection in contemporary societies.